The Traumatic Nasal Deformity - Marcus, Benjamin C. (Facial Plastic Surgery, 2020)
One of the most challenging aspects of rhinoplasty is correction of the posttraumatic nasal deformity. This special set of cases included challenges in managing the difficult septum, complicated nasal bones, and special considerations such as the septal perforation.
Keywords: rhinoplasty; osteotomies; septoplasty